2011
DOI: 10.1002/uog.8911
|View full text |Cite
|
Sign up to set email alerts
|

Universal cervical‐length screening to prevent preterm birth: a cost‐effectiveness analysis

Abstract: Objective To determine whether routine measurement of second-trimester transvaginal cervical length by ultrasound in low-risk singleton pregnancies is a costeffective strategy. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 26 publications
3
125
1
10
Order By: Relevance
“…(26) Two cost-effectiveness analyses evaluating universal cervical length screening in singleton gestations, to identify those with short CL eligible for vaginal progesterone, have been published so far. (27,28) Both reported that such a strategy would be cost-effective. In one study, compared to other managements, including no screening, 'universal' sonographic screening of CL in singletons was predicted to results in a reduction of 95,920 preterm births < 37 weeks annually in the US, and was actually cost-saving (almost $13 billion saved).…”
Section: Vaginal Progesteronementioning
confidence: 99%
See 1 more Smart Citation
“…(26) Two cost-effectiveness analyses evaluating universal cervical length screening in singleton gestations, to identify those with short CL eligible for vaginal progesterone, have been published so far. (27,28) Both reported that such a strategy would be cost-effective. In one study, compared to other managements, including no screening, 'universal' sonographic screening of CL in singletons was predicted to results in a reduction of 95,920 preterm births < 37 weeks annually in the US, and was actually cost-saving (almost $13 billion saved).…”
Section: Vaginal Progesteronementioning
confidence: 99%
“…the cost of vaginal progesterone or of TVU screening), universal screening was cost-effective over 99% of the time. (28) This costeffectiveness analysis initially addressed only women with a TVU CL ≤ 1.5 mm. In an addendum, the authors mention that a re-analysis adding progesterone treatment for women with TVU CL between 1.6 to 2.5 mm did not change their conclusions, with the details of the reanalysis not provided.…”
Section: Vaginal Progesteronementioning
confidence: 99%
“…In some other technologies, such as drugs, this may not be the case, and for those, costs and effects for all prevalent cohorts that use the technology have to be summed up for each period. The model was populated with data from previous cost-effectiveness analyses (21,22), and ongoing studies on technology T1 as well as some simplifying…”
Section: The Effect Of the Dynamic Model On Value Of Information Analmentioning
confidence: 99%
“…For women with a prior PTD treated with 17OHP-C, the projected discounted lifetime medical costs of their offspring could be reduced by more than 2 billion dollars annually (Bailit &Votruba, 2007). Three U.S. cost-effective analysis studies using decision analysis have been published (Odibo et al, 2006;Cahill et al, 2010;Werner et al, 2011). Odibo et al (Odibo et al, 2006) compared the cost-effectiveness of using 17OHP-C for the prevention of PTD in cost-savings in women with prior PTD results in cost-savings in women with prior PTD less than 32 weeks and 32 to 37 weeks' gestation.…”
Section: Costmentioning
confidence: 99%
“…The calculated annual cost, based on spontaneous PTBs < 34 weeks' gestation and severe morbidity prevented, fell from $46.2 billion to $33.3 billion annually, an annual saving of $12.9 billion, which was greater than calculated savings from 17OHP-C treatment on the basis of maternal history ($7.9 billion) or cervical-length screening in high risk pregnancies ($3.9 billion). Using a mean estimate of $70 for the second trimester CL scan and $206 for vaginal progesterone treatment, Werner et al (Werner, 2011) analyze their model using data of Fonseca et al (Fonseca et al, 2007), the cost saving was $12.1 million for every 100,000 women in the universal screened/vaginal progesterone group. Whereas, using data of Hassan et al (Hassan et al, 2011), the cost saving was $19.6 million per every 100,000 women.…”
Section: Costmentioning
confidence: 99%